6p+6=5p+14

Simple and best practice solution for 6p+6=5p+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+6=5p+14 equation:


Simplifying
6p + 6 = 5p + 14

Reorder the terms:
6 + 6p = 5p + 14

Reorder the terms:
6 + 6p = 14 + 5p

Solving
6 + 6p = 14 + 5p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-5p' to each side of the equation.
6 + 6p + -5p = 14 + 5p + -5p

Combine like terms: 6p + -5p = 1p
6 + 1p = 14 + 5p + -5p

Combine like terms: 5p + -5p = 0
6 + 1p = 14 + 0
6 + 1p = 14

Add '-6' to each side of the equation.
6 + -6 + 1p = 14 + -6

Combine like terms: 6 + -6 = 0
0 + 1p = 14 + -6
1p = 14 + -6

Combine like terms: 14 + -6 = 8
1p = 8

Divide each side by '1'.
p = 8

Simplifying
p = 8

See similar equations:

| z+0.9=3.1 | | x(2-12-3m)=-8-2m | | r(1.4+35)=436.60 | | 4x-7=59-7x | | x-1/4=5 | | 2xc+-1c^2x+x=-10+5c | | 4x-3-4=24 | | x+2cx-c^2x=-10+5c | | X^2-25-144=0 | | (6*6-3*3*3)/7 | | (u^4/-2w^2)^2 | | -56=y-49 | | -67=-32n+29 | | 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 | | 8.5x-6.5=6.8x+10.0 | | 6(v+3)-2v=2(2v+1)-11 | | 12x-3(3x-6)=2x+2 | | 25=13+8d | | 240=170+5d | | 10f+5= | | -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 |

Equations solver categories